2016
DOI: 10.1590/0103-8478cr20151140
|View full text |Cite
|
Sign up to set email alerts
|

Plant extracts, metaldehyde and saline solutions on the population control of Bradybaena similaris

Abstract: Plant extracts, metaldehyde and saline solutions on the population control of Bradybaena similaris.Ciência Rural, v.46, n.8, ago, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…In addition, this pest has also been reported as intermediate hosts of trematodes and nematodes ( Alves et al, 2014 ; Morassutti et al, 2014 ), and it has been one of known intermediate hosts of Angiostrongylus cantonensis in China ( Shan et al, 2008 ). Chemical molluscicides, such as niclosamide and metaldehyde, are usually applied to control snails ( Lutinski et al, 2016 ; Wu et al, 2018 ). However, application of chemical agents to control pests is not sustainable due to low selectivity to target pest, resulting in pesticide resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this pest has also been reported as intermediate hosts of trematodes and nematodes ( Alves et al, 2014 ; Morassutti et al, 2014 ), and it has been one of known intermediate hosts of Angiostrongylus cantonensis in China ( Shan et al, 2008 ). Chemical molluscicides, such as niclosamide and metaldehyde, are usually applied to control snails ( Lutinski et al, 2016 ; Wu et al, 2018 ). However, application of chemical agents to control pests is not sustainable due to low selectivity to target pest, resulting in pesticide resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, application of chemical agents to control pests is not sustainable due to low selectivity to target pest, resulting in pesticide resistance. Moreover, it can contaminate the environment and affect the beneficial animals ( Lutinski et al, 2016 ; Tunholi et al, 2017 ). Recently, studies were reported showing that plant-derived molluscicides have obviously molluscicidal activity in the laboratory ( Jia et al, 2019 ; Ke et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…& Bessa, 2001;Junqueira et al, 2003;Carvalho et al, 2008). Essa espécie habita os cultivos hortícolas, podendo eventualmente ser praga de hortaliças folhosas(Souza, 1999;Lutinski et al, 2016). Os indivíduos se alimentam de folhagem e matéria vegetal morta e vivem em média occurred from July to September and from January to March, with clear generational overlap.…”
unclassified